Comparison of the health related physical fitness of adults of differents ages - Juliano Casonatto; Ferdinando Oliveira Carvalho; David Ohara; Edilson Serpeloni Cyrino; David Augusto dos Reis; Isabel Cristina Brisotti dos Reis; Douglas Fernando Dias; Mathias Roberto Loch (Universidade Federal de Santa Catarina, 2008)
objective of this study was to investigate possible differences in the levels of health related physical fitness of men and women of different ages. The sample comprised 326 people (132 men and 194 women) who did not perform regular physical exercise, and who were separated for analysis by sex and into three age groups: 20-29 years (G1), 30-39 years (G2) and 40-49 years (G3). All subjects underwent anthropometric measurements and motor performance testing (flexibility, muscle resistance/strength and cardiorespiratory fitness). Statistical analysis employed the Levene test to verify the homogeneity of variation, descriptive statistics, single factor ANOVA (age group) and the Bonferroni test. The significance level adopted was p<0.05. The best levels of physical fitness were observed among the youngest subjects (G1), irrespective of sex, while the worst fitness levels were detected in the oldest subjects (G3). The variation in body fat from G1 to G3 was more accentuated among the men (34%) than among the women (16%). With relation to motor performance, the greatest percentage differences between G1 and G3 were detected by either modified abdominal test (39%and 22%, for men and women respectively) and the arm flexion and extension test(31% and 24%, for men and women respectively. The results suggest that among individuals who do not regularly practice physical exercise there is a natural tendency for health related physical fitness to reduce as age increases. Resumo O objetivo deste estudo foi investigar as possíveis diferenças nos níveis de aptidão física relacionada à saúde (AFRS) em homens e mulheres de diferentes faixas etárias. Fizeram parte da amostra 326 sujeitos (132 homens e 194 mulheres), não-praticantes de exercícios físicos regulares, que foram separados, de acordo com o sexo, em três grupos etários: 20-29 anos (G1), 30-39 anos (G2) e 40-49 anos (G3). Todos os sujeitos foram submetidos a medidas antropométricas e de desempenho motor (flexibilidade, resistência/força muscular e aptidão cardiorrespiratória). A análise estatística incluiu o teste de Levene para verificação da homogeneidade das variâncias, estatística descritiva, ANOVA de um fator (faixa etária) e o teste de Bonferroni. O nível de significância adotado foi de P<0,05. Os melhores níveis de aptidão física, tanto nos homens quanto nas mulheres, foram observados nos sujeitos mais jovens (G1), enquanto que os piores níveis foram encontrados nos sujeitos de idade mais avançada (G3). A variação da gordura corporal relativa do G1 para o G3 foi mais acentuada nos homens (34%) do que nas mulheres (16%). Em relação ao desempenho motor, as maiores diferenças percentuais entre G1 e G3 foram identificadas no teste abdominal modifi cado (39% vs. 22% para homens e mulheres, respectivamente) e flexão e extensão de braço (31% vs. 24% para homens e mulheres, respectivamente). Os resultados sugerem que existe uma tendência natural de redução dos níveis de AFRS com o avançar da idade, em indivíduos não praticantes de exercícios físicos regulares.